‘Misclassified Partnership’ and the Impact of Legal Loophole on Workers - Nabiyla Risfa Izzati; Mas Muhammad Gibran Sesunan (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2022)
In Indonesia, the partnership model was previously popularized by gig companies. However, now it is spreading into various businesses, such as e-commerce, shipping, and start-up industries. Over the years, the extensive use of the partnership model is becoming problematic as it transforms into a